PCR-based methods to the diagnosis of imported malaria - Berry A.; Benoit-Vical F.; Fabre R.; Cassaing S.; Magnaval J.F. (Parasite, 2008)
Rapid and precise diagnosis of malaria is needed to take care febrile patient returning from endemic areas. Since the first description of the diagnosis of Plasmodium infection by polymerase-chain-reaction (PCR), the role of this kind of molecular method in the laboratory diagnosis of imported malaria is still a topical question. PCR-based assays were found to be more sensitive and more specific than all conventional methods. The highest contribution of the molecular diagnosis is that a PCR negative result would ascertain the lack of any malaria infection, thus quickly orienting the investigations toward other aetiology. This technique should be now considered as the gold standard for the diagnosis of imported malaria.